Visual Field Loss Morphology in High- and Normal-Tension Glaucoma - Michele Iester; Fabio De Feo; Gordon R. Douglas (Journal of Ophthalmology)
Purpose. To determine whether the patterns of visual field damage between high-tension glaucoma (HTG) and normal-tension glaucoma (NTG) are equivalent. Methods. In this retrospective cross-sectional study, fifty-one NTG and 57 HTG patients were recruited. For each recruited patient only the left eye was chosen. Glaucomatous patients had abnormal visual fields and/or glaucomatous changes at the optic nerve head. They were classified as HTG or NTG on the basis of intraocular pressure (IOP) measurements. Patients' visual fields were analyzed by using Humphrey Field Analyzer (HFA), program 30-2, full threshold. The visual field sensitivity values and the pattern deviation map values of the 72 tested points were considered. Then a pointwise analysis and an area analysis, based on the Glaucoma Hemifield test criteria, were performed, and a comparison between the two subgroups was made by Student’s t test. Results. Between NTG and HTG, no significant difference was found pointwise for almost all the visual field points, except for two locations. One was under the blind spot, and the other was in the inferior hemifield around the twenty-degree position. When area analysis was considered, three areas showed a significantly different sensitivity between HTG and NTG. Conclusions. These data suggested that there was no relevant difference in the pointwise analysis between NTG and HTG; however, when visual field areas were compared, no difference in paracentral areas was found between NTG and HTG, but superior nasal step and inferior and superior scotomata showed to be deeper in HTG than in NTG.